Palladium‐Catalyzed C(sp2)−H Alkylation of Aldehyde‐Derived Hydrazones with Functionalized Difluoromethyl Bromides. Issue 5 (16th December 2015) - Prieto, Alexis; Melot, Romain; Bouyssi, Didier; Monteiro, Nuno
Abstract: A palladium‐catalyzed C(sp 2 )−H difluoromethylation of aldehyde‐derived hydrazones using bromodifluoromethylated compounds to afford the corresponding functionalized difluoromethylketone hydrazones has been established. It is proposed that a radical/SET mechanism proceeding via a difluoroalkyl radical may be involved in the catalytic cycle. Applications of the methodology to the synthesis of α, α‐difluoro‐β‐ketoesters and α, α‐difluoroketones (RCOCF2 H) have been illustrated. Abstract : Single file : The title reaction was established as a new and versatile synthetic entry to α, α‐difluoro carbonyl compounds. On the basis of preliminary studies, the proposed mechanism involves a radical/single‐electron transfer process via a difluoroalkyl radical intermediate.